Reconstructing Linguistic Landscapes in Time and Space at the Railways in South Africa - Johnson , Ian Lyndon (Research Highlights in Language, Literature and Education Vol. 3, 2023)
Rail transport is the backbone of mobility in South Africa, attracting diverse commuters from various sociocultural and economic backgrounds. This paper explores the transformation of the linguistic landscape (LL) in South Africa since the end of apartheid as perceived and experienced by rail commuters. The guiding research objective was to assess the LL through the lenses of rail commuters over time. Interviews were conducted to assess commuter perceptions and experiences of changes in the languages used on signs at the railways since the end of apartheid. Interviews were analysed using thematic content analysis, supplemented with multimodal analyses of signs. Key findings reveal that although signs about racial segregation were removed from the LL since the end of apartheid, many people today still remember those signs and continue to act upon the messages that were displayed on the apartheid signs as if they remain physically emplaced. The findings suggest that messages about racial segregation in the LL had become embedded in people’s minds. In this way, the paper contributes to the notion of ‘oralinguascaping’ in which people rely on both memory and oral language for sign-making thereby contrasting traditional theorising on LL that is mainly premised on written or scripted languages or texts.